Episomal and chromosomal DNA replication and recombination in Entamoeba histolytica - Bhattacharya, Sudha (Frontiers in Molecular Biosciences, 2023)
Entamoeba histolytica is the causative agent of amoebiasis. DNA replication studies in E. histolytica first started with the ribosomal RNA genes located on episomal circles. Unlike most plasmids, Entamoeba histolytica rDNA circles lacked a fixed origin. Replication initiated from multiple sites on the episome, and these were preferentially used under different growth conditions. In synchronized cells the early origins mapped within the rDNA transcription unit, while at later times an origin in the promoter-proximal upstream intergenic spacer was activated. This is reminiscent of eukaryotic chromosomal replication where multiple potential origins are used. Biochemical studies on replication and recombination proteins in Entamoeba histolytica picked up momentum once the genome sequence was available. Sequence search revealed homologs of DNA replication and recombination proteins, including meiotic genes. The replicative DNA polymerases identified included the α, δ, ε of polymerase family B; lesion repair polymerases Rev1 and Rev3; a translesion repair polymerase of family A, and five families of polymerases related to family B2. Biochemical analysis of EhDNApolA confirmed its polymerase activity with expected kinetic constants. It could perform strand displacement, and translesion synthesis. The purified EhDNApolB2 had polymerase and exonuclease activities, and could efficiently bypass some types of DNA lesions. The single DNA ligase (EhDNAligI) was similar to eukaryotic DNA ligase I. It was a high-fidelity DNA ligase, likely involved in both replication and repair. Its interaction with EhPCNA was also demonstrated. The recombination-related proteins biochemically characterized were EhRad51 and EhDmc1. Both shared the canonical properties of a recombinase and could catalyse strand exchange over long DNA stretches. Presence of Dmc1 indicates the likelihood of meiosis in this parasite. Direct evidence of recombination in Entamoeba histolytica was provided by use of inverted repeat sequences located on plasmids or chromosomes. In response to a variety of stress conditions, and during encystation in Entamoeba invadens, recombination-related genes were upregulated and homologous recombination was enhanced. These data suggest that homologous recombination could have critical roles in trophozoite growth and stage conversion. Availability of biochemically characterized replication and recombination proteins is an important resource for exploration of novel anti-amoebic drug targets.